Effectiveness of Telemedicine in Reducing Hospitalizations in Patients Discharged from the Hospital Due to Heart Failure: A Randomized Clinical Trial Protocol - Ribeiro,Edmar Geraldo (2022)
Abstract Fundament: Telemedicine for follow-up in heart failure (HF) patients is effective in reducing hospitalizations, total and cardiovascular mortality. However, few studies were conducted in low and middle income, where lower access to technology and illiteracy could impact the results. Objective: To assess the effectiveness of associating telemedicine strategies, when compared to usual care, in reducing hospitalizations related to HF in patients discharged from the hospital due to HF. Methods: Controlled, randomized, multicenter, parallel-arm clinical trial, with an allocation ratio of 1:1, blinded to outcome evaluation, in which 340 patients who were discharged from public hospitals in Belo Horizonte due to HF will be randomized. Patients will be followed for 6 months and the intervention group will receive, in addition to the usual care, Structured Telephone Support (STS) from a nurse, a doctor, and an educational program. Counseling will be according to a clinical decision tree. The level of significance in the statistical analysis will be 5%. Expected results: Reduction in the number of hospital readmissions and/or in hospitalization time, in addition to developing a software with a clinical decision tree for remote follow-up and patient education about HF adapted to local culture. Conclusions: The intention of this study is to develop a telemedicine strategy and assess whether or not, in addition to the usual care, it is effective in reducing hospitalizations and mortality from HF. If effective, the aforementioned strategy could reduce costs and hospital needs in the Unified Health System (SUS, in Portuguese) for patients with HF. These results will be even more relevant considering the pandemic of COVID-19.